BARUS AND CAMPHOR IN THE EARLY HISTORY OF ISLAM IN NUSANTARA - Nurfaezal Nurfaezal (Asia-Pacific Journal on Religion and Society, 2021)
The seminar on the entry of Islam into the archipelago in Medan in 1963 has resulted in a decision that Islam had reached the west coast of Sumatra in the 7th century AD, brought by Arab traders. The arrival of Arab traders to the west coast, precisely at the trading port known in the literature as Barus or Fansur, was not to spread Islam. Long before, in fact, they had already arrived in Barus to trade. Among the trade commodities they sought were camphor, frankincense and gold. This means that Barus and camphor had indirectly "invited" the entry of Islam into the archipelago in the early days of Islam through Muslim Arab traders.